Artificial Feeding of Ornithodoros fonsecai and O. brasiliensis (Acari: Argasidae) and Investigation of the Transstadial Perpetuation of Anaplasma marginale - Castro-Santiago, Ana Carolina; Lima-Duarte, Leidiane; Camargo, Jaqueline Valeria [UNESP]; De Almeida, Beatriz Rocha [UNESP]; Simons, Simone Michaela; Mathias, Luis Antonio [UNESP]; Bassini-Silva, Ricardo [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; Barros-Battesti, Darci Moraes [UNESP] (MDPI, 2023)
Anaplasma marginale is a Gram-negative, obligate intraerythrocytic bacterium that causes bovine anaplasmosis. While hard ticks of the genera Dermacentor and Rhipicephalus can be biological vectors, transmitting this pathogen via saliva during blood meals, blood-sucking insects, and fomites play a role as mechanical vectors. Little is known about the interaction between Anaplasma marginale and Argasidae ticks. Among soft ticks, Ornithodoros fonsecai (Labruna and Venzal) and Ornithodoros brasiliensis Aragão inhabit environments surrounding localities where many cases of bovine anaplasmosis have been reported. Ticks of the species O. fonsecai parasitize bats, while O. brasiliensis can parasitize different vertebrate species. Therefore, the present study aimed to feed third-instar nymphs artificially (N3) of O. fonsecai and O. brasiliensis using blood samples obtained from a calf naturally infected with A. marginale and rabbit blood added to A. marginale-containing bovine erythrocytes, to investigate the ability of these nymphs to acquire, infect and transstadially perpetuate this agent. For the artificial feeding system, adapted chambers and parafilm membranes were used. Nymphs of both tick species were submitted to different replications weighed before and after each feeding. Blood samples and molted ticks were submitted to DNA extraction, quantitative real-time PCR for the msp1β gene to detect A. marginale DNA, while a semi-nested polymerase chain reaction for the msp1α gene was performed for genotyping. Using calf blood naturally infected with A. marginale, among the three artificial feeding replications performed with O. fonsecai and O. brasiliensis nymphs, the DNA of A. marginale was detected in both nymphs after 30–50 days of molting. For artificial feeding with rabbit blood added to bovine erythrocytes containing A. marginale, the DNA of this pathogen was also detected in both nymph species. As for the assay for the msp1α gene, strains were found Is9; 78 24-2; 25; 23; α; and β. It was concluded that nymphs (N3) of O. fonsecai and O. brasiliensis could feed artificially through a parafilm membrane using blood from calves and rabbits infected by A. marginale. The DNA of A. marginale was detected in nymphs fed artificially of both tick species studied after molt. However, further studies are needed to confirm transstadial perpetuation in other instars and their host transmission capacity.
Keywords: argasid ticks; biology; bovine anaplasmosis; transmission